Ancient pathogen DNA in human teeth and petrous bones. Issue 6 (26th February 2018) - Margaryan, Ashot; Hansen, Henrik B.; Rasmussen, Simon; Sikora, Martin; Moiseyev, Vyacheslav; Khoklov, Alexandr; Epimakhov, Andrey; Yepiskoposyan, Levon; Kriiska, Aivar; Varul, Liivi; Saag, Lehti; Lynnerup, Niels; et al.
Abstract: Recent ancient DNA (aDNA) studies of human pathogens have provided invaluable insights into their evolutionary history and prevalence in space and time. Most of these studies were based on DNA extracted from teeth or postcranial bones. In contrast, no pathogen DNA has been reported from the petrous bone which has become the most desired skeletal element in ancient DNA research due to its high endogenous DNA content. To compare the potential for pathogenic aDNA retrieval from teeth and petrous bones, we sampled these elements from five ancient skeletons, previously shown to be carrying Yersinia pestis . Based on shotgun sequencing data, four of these five plague victims showed clearly detectable levels of Y. pestis DNA in the teeth, whereas all the petrous bones failed to produce Y. pestis DNA above baseline levels. A broader comparative metagenomic analysis of teeth and petrous bones from 10 historical skeletons corroborated these results, showing a much higher microbial diversity in teeth than petrous bones, including pathogenic and oral microbial taxa. Our results imply that although petrous bones are highly valuable for ancient genomic analyses as an excellent source of endogenous DNA, the metagenomic potential of these dense skeletal elements is highly limited. This trade‐off must be considered when designing the sampling strategy for an aDNA project. Abstract : In this study we measure the yield of ancient pathogen DNA retrieved from human teeth and petrous bones. We demonstrate that known ancient plague victims have Y. pestis DNA in their teeth but not in their petrous bones. We show that this reflects a general metagenomic difference between the two substrates. This has implications when designing the sampling strategy in ancient DNA projects.